Analisis Pengaruh Kedalaman Potong terhadap Getaran dan Kekasaran Permukaan pada Proses Bubut Material Baja Karbon ST37 - Rafi Malik, Abdur; Anam, Chairul; Wahid, M Abdul; Muzaka, Khairul; Novita Sari, Eli (Jurnal Rekayasa Mesin, 2024)
Machine tools play an integral role in the industrial production process, including the manufacturing and repair of components. One of the commonly used machines in the manufacturing industry is a lathe, which is used to cut a rotating workpiece using a tool. One type of steel that is often used is ST 37 steel, which has a carbon content of less than 0.3%. Although highly ductile, the surface hardness of the steel is low and requires modification before being used for certain applications such as the construction of machinery that rubs against each other. Vibration in machinery can cause discomfort, lack of accuracy in measurement, or even damage to the machine. The surface roughness characteristics of the workpiece are also influenced by cutting conditions and cutting tool geometry. Therefore, this study aims to analyze the effect of variations in depth of cut on vibration and surface roughness in the lathe process of carbon steel material ST 37. The results of the research on vibration testing obtained the vibration speed value is influenced by the depth of cut. The greater the depth of cut, the higher the vibration speed, while the smaller the depth of cut, the lower the vibration speed, While the surface roughness test at a depth of cut variation of 0.4 mm, 0.5 mm, and 0.6 mm is obtained with the average value of the HSS tool surface roughness of 2.128 µm, 3.841 µm, and 4.032 µm, respectively.